The effect of sugar concentration and temperature on growth and volatile phenol production by Dekkera bruxellensis in wine - Barata, André (2013)
The wine spoilage yeast Dekkera bruxellensis was evaluated for the production of 4-ethylphenol under low concentrations (0.02–20 g L 1) of glucose and fructose in synthetic media. Measurable amounts of 4-ethylphenol were produced over 0.2 g L 1 of each sugar. The yeast growth rate and amount of biomass formed increased from 0.2 to 20 g L 1 of glucose or fructose, being accompanied by increasing production of 4-ethylphenol. In red wines, the production of 4-ethylphenol was only observed in the presence of growing populations of indigenous or inoculated strains of D. bruxellensis. The production rate of 4-ethylphenol varied between 22 and 93 mg day 1 either with inoculated strains or wild populations in bottled wines. The production rate of 4-ethylphenol as a function of the increase in the number of cells varied from 349 to 1882 mg L 1 per one log CFUmL 1. The effect of temperature on cellular viability and 4-ethylphenol production was tested in red wines with indigenous or inoculated strains of D. bruxellensis. Incubation temperatures of 15, 20 and 25 1C allowed cellular growth and volatile phenol production. Increasing incubation temperatures to 36 1C induced full viability loss of 10 strains of D. bruxellensis within <12 h.